2013
DOI: 10.1371/journal.pone.0077335
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the eIF2α Kinase GCN2 Fails to Rescue the Memory Decline Associated with Alzheimer’s Disease

Abstract: Emerging evidence suggests that dysregulated translation through phosphorylation of eukaryotic initiation factor-2α (eIF2α) may contribute to Alzheimer’s disease (AD) and related memory impairments. However, the underlying mechanisms remain unclear. Here, we crossed knockout mice for an eIF2α kinase (GCN2: general control nonderepressible-2 kinase) with 5XFAD transgenic mice, and investigated whether GCN2 deletion affects AD-like traits in this model. As observed in AD brains, 5XFAD mice recapitulated signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 40 publications
4
55
2
Order By: Relevance
“…Genotyping was performed by PCR analysis of tail DNA and all experiments were done blind with respect to the genotype of mice. In this study, we investigated the effects of PERK haploinsufficiency in 5XFAD mice at 8–9 months of age, which exhibit significant elevations in BACE1 and ATF4 expression (Devi and Ohno, 2010a; Devi and Ohno, 2013a; Zhao et al, 2007). Since our previous study shows that there is no sex difference in cerebral Aβ levels in 5XFAD mice except for the younger age (≤3 months) (Oakley et al, 2006), a similar number of males and females were used for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping was performed by PCR analysis of tail DNA and all experiments were done blind with respect to the genotype of mice. In this study, we investigated the effects of PERK haploinsufficiency in 5XFAD mice at 8–9 months of age, which exhibit significant elevations in BACE1 and ATF4 expression (Devi and Ohno, 2010a; Devi and Ohno, 2013a; Zhao et al, 2007). Since our previous study shows that there is no sex difference in cerebral Aβ levels in 5XFAD mice except for the younger age (≤3 months) (Oakley et al, 2006), a similar number of males and females were used for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…*p Ͻ 0.05 compared with the no-retrieval (NoR) group. ugation for 8 min at 4°C to remove any insoluble materials, including nuclei and large debris, and the supernatant containing cytosolic proteins and light membrane fraction was collected based on previous studies (Jiang et al, 2010;Devi and Ohno, 2013). All of the procedures were performed at 0 -4°C.…”
Section: Methodsmentioning
confidence: 99%
“…A link between Alzheimer’s disease (AD) and reduced global translation was established in 1989, when Langstrom et al demonstrated that polysomes from the cortices of AD patients were associated with less RNA than those from controls. Subsequently, increased levels of p-eIF2α were found in the cortex and hippocampus of AD patients and in AD mouse models (Chang et al, 2002b; Devi and Ohno, 2013; Hoozemans et al, 2009; Kim et al, 2007; Lewerenz and Maher, 2009; Ma et al, 2013; Mouton-Liger et al, 2012; O’Connor et al, 2008; Page et al, 2006; Stutzbach et al, 2013; Unterberger et al, 2006). In addition to AD, p-eIF2α levels are elevated in the brain or spinal cord of patients and mice with prion disease (Unterberger et al, 2006), amyotrophic lateral sclerosis (ALS; Ilieva et al, 2007), Parkinson’s disease (PD; Hoozemans et al, 2007, 2012), Huntington’s disease (HD; Leitman et al, 2014), and various tauopathies (Köhler et al, 2014; Nijholt et al, 2012; Radford et al, 2015; Stutzbach et al, 2013; Unterberger et al, 2006).…”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 99%
“…Similarly, a reduction in p-eIF2α levels and improved spatial memory were observed when Gcn2 was deleted in an AD mouse model. In contrast, GCN2 activation appears to be protective in a different AD mouse model; in this context, loss of Gcn2 increases p-PERK, increasing levels of p-eIF2α and the burden of Aβ plaques in the brain (Devi and Ohno, 2013). …”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 99%